Nanog, Stat-3, and Sox-5 involvement in human fetal temporomandibular joint late development - Tacia Catharine Pagni; Juliana Malta da Cunha; Daniel Martinez Saez; Adriana da Costa-Neves; Irina Kerkis; Marcelo Cavenaghi Pereira da Silva (Elsevier, 2023)
Background and aim: The temporomandibular joint (TMJ) is a synovial joint that allows the complex movements essential for life. It connects the jawbone to the skull, working as a sliding hinge. Moreover, pluripotent stem cells are a source of precursors and tissue-specific cells in developing organisms, however, their biodistribution in developing fetal tissues is weakly studied. The aim of our study was analyse immunohistochemical expression of Nanog, Oct-4, Sox-2 and Stat-3 and Sox-5, in TMJ tissue samples from human fetuses aged between the 12th and 20th weeks of intrauterine life. Materials and methods: We fixed and processed TMJ tissue samples from human fetuses, histological sections and immunohistochemical procedures were carried out. Results: TMJ histological studies examination did not reveal any difference in the tissue organization between the samples in the studied periods. Immunohistochemical analysis demonstrated that Oct-4 and Sox-2 lack their expression in TMJ. In contrast, Nanog was expressed in nucleous of proliferative layer of mandibular condyle, Stat-3 was expressed in nuclear cells of articular disc, Stat-3 and Sox-5 showed positive nuclear and cytoplasmic immunostaining in codrocyte layers and in ossification areas. Conclusions: Nanog acts in maintanence of pluripotency, Stat-3 in articular disc acts as a transcriptional factor. Stat-3 and Sox-2 act in chondrocyte and osteoblast diferentiation. Distribution of the cells, which express Nanog, Stat-3, and Sox-5 in TMJ tissue during fetal development, can help further understand its physiology, pathology, and repairing capacities.